1Simulation and experimental research on multi-pass cutting of nickel-based alloy by WEDM-LS - Xin Wu; Tao Lu; Peng Zhao; Yigang Wang; Kui Zhang; Xiaoxing Chen (AIP Advances)
Wire Electrical Discharge Machining-Low Speed (WEDM-LS) offers high precision and flexibility for machining nickel-based alloys but is limited to aerospace applications due to surface property degradation caused by the recast layer. To investigate surface property formation in multi-pass WEDM-LS, an integrated experimental and simulation-based approach was used. Experiments revealed that the recast layer, composed of high-temperature oxidation products rich in carbon (C) and oxygen (O), could be minimized using a “Cut-1-Finish-3” strategy, achieving a surface roughness of 0.35 μm and a recast layer thickness of 1 μm. A simulation model further clarified that discharge energy during rough machining determines pit depth and recast layer thickness, while finishing passes refine the surface by removing protrusions and thinning the layer. The overlapping effect of electric erosion pits was proposed to explain surface morphology formation, highlighting the complementary roles of rough and finish machining in optimizing surface quality.